The lived experiences of pediatric nursing students following high-fidelity simulations and problem-based learning sessions - Sadeg Aldolaim; Latifa Abdullah Aldossary; Ibtihal Abdulhadial Almomin; Areej Abdulghani Haitham (BMC Nursing)
Abstract Background Nursing students often find transitioning from classroom learning to clinical practice to be a challenging process, particularly in pediatric care where direct patient contact can be limited. High-fidelity simulation (HFS) and problem-based learning (PBL) have emerged as innovative educational approaches to help bridge this gap, offering students safe, structured environments to develop clinical competence. Methods This qualitative study explored the lived experiences of final-year pediatric nursing students who participated in HFS and PBL during their clinical rotations. Semi-structured interviews were conducted, and data were analyzed using Moustakas’ transcendental phenomenological method. The study followed COREQ guidelines to ensure methodological transparency and rigor. Results Four themes emerged from the data: (1) Benefits of HFS and PBL, describing enhanced clinical confidence, decision-making, and practical skills; (2) Effect of Integrative Learning, highlighting the meaningful connection between theory and practice through guided reflection and teamwork; (3) Challenge to Respond to the Real Child, reflecting students’ concerns about applying simulation-learned skills in emotionally demanding pediatric settings; and (4) Necessity of Collaboration, underscoring the importance of interdisciplinary engagement and broader clinical exposure. Conclusion This study demonstrates how HFS and PBL can enhance students’ preparation for pediatric clinical practice, enabling them to develop into competent and compassionate professionals. At the same time, the findings point to key areas for improvement, such as increasing simulation realism, strengthening faculty facilitation skills, and incorporating culturally responsive communication scenarios. A more intentional curriculum design, ongoing faculty development, and collaborative, interdisciplinary learning opportunities can be derived from these insights. Grounded in experiential learning theory, these strategies offer a pathway toward more holistic and contextually relevant nursing education. Clinical trial number Not applicable.